2016
DOI: 10.32598/jccnc.2.3.135
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Fear of Falling and Functional Independence in Older Adult Living in an Iranian Nursing Home: A Cross-Sectional Study

Abstract: Background: Fear of falling is common amongst older adults, especially those who live in nursing homes. This study aimed to determinate factors associated with fear of falling and functional independence in older adults living in nursing homes. Methods: This was a cross-sectional study using a convenience sampling method to enroll 200 older adults living in nursing homes from 25 senior centers in Tehran (districts 1 and 2) between September 2015 and November 2015. Main outcome measurement instruments were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…12) Falling is a serious issue in community-dwelling adults as the resulting psychological consequences may lead to mobility deficits and reduced quality of life. 13) This mental injury results from a fear of falling, which cause social isolation in older adults. 1) Many studies have reported a fear of falling as an essential factor for falls.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…12) Falling is a serious issue in community-dwelling adults as the resulting psychological consequences may lead to mobility deficits and reduced quality of life. 13) This mental injury results from a fear of falling, which cause social isolation in older adults. 1) Many studies have reported a fear of falling as an essential factor for falls.…”
Section: Introductionmentioning
confidence: 99%
“…1) Many studies have reported a fear of falling as an essential factor for falls. [12][13][14] Moreover, fear of falling is a crucial factor related to reduced life satisfaction and increased nursing home admission rates. 2,14) Fear of falling or post-fall syndrome is defined as "an ongoing concern about falling and fall-related dangerous complications".…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low bone mass and loss of bone microarchitecture quality are characteristics of osteoporosis, which leads to higher bone fracture risk. Many people above 65 years are at risk of falling and this rate increases with age (Bastani et al 2016).…”
Section: Introductionmentioning
confidence: 99%